1984
DOI: 10.1038/310501a0
|View full text |Cite
|
Sign up to set email alerts
|

A low voltage-activated, fully inactivating Ca channel in vertebrate sensory neurones

Abstract: Calcium channels in excitable membranes are essential for many cellular functions. Recent analyses of the burst-firing mode of some vertebrate neurones suggest that changes in their functional state are controlled by a Ca conductance that is largely inactivated at resting membrane potentials (-50 to -60 mV), but becomes activated following a conditioning hyperpolarization of the cell membrane. Here, using chick and rat sensory neurones, we present evidence for a new type of Ca channel with time- and voltage-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
370
3
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 819 publications
(406 citation statements)
references
References 14 publications
28
370
3
5
Order By: Relevance
“…HVA Ca 2+ currents had mean amplitudes of 196.6 ± 16.6 pA at +10 mV (n = 81) that normalized for the cell capacitance (33.2 ± 3.2 pF; n = 81) gave mean current densities of 5.9 ± 0.8 pA/pF. The T-type channels had the typical gating characteristics described in these [28] and other neurons [34]. They activated below −40 mV, had voltage-dependent activation and fast inactivation and were inactivated at V h around −50 mV.…”
Section: Expression Of Cb1r and Cb2r In Gt1-7 Neuronsmentioning
confidence: 82%
“…HVA Ca 2+ currents had mean amplitudes of 196.6 ± 16.6 pA at +10 mV (n = 81) that normalized for the cell capacitance (33.2 ± 3.2 pF; n = 81) gave mean current densities of 5.9 ± 0.8 pA/pF. The T-type channels had the typical gating characteristics described in these [28] and other neurons [34]. They activated below −40 mV, had voltage-dependent activation and fast inactivation and were inactivated at V h around −50 mV.…”
Section: Expression Of Cb1r and Cb2r In Gt1-7 Neuronsmentioning
confidence: 82%
“…2a). Second, the relationships of capacitance changes and quantity of charge vs voltage [ΔC(V) and Q(V)] do not show "double peaks" as for the I/V characteristics [11][12][13] but rather a sharp broadening due to the constant contribution of T-type channels to both ΔC(V) and Q(V) over a wide range of voltages (Fig. 2b).…”
Section: T-type Channels and Fast Capacitance Changes In Rat Melanotrmentioning
confidence: 99%
“…It was indeed few years after the publication of the famous Pfluegers Archiv's article [28] that several groups could identify and describe the unique properties of LVA channels [2,4,6,11,12,22,48,50].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Functionally, the Ca 2C current responsible for this depolarization was rapidly recognized as one of the key conductances underlying the characteristic rhythmic high-frequency burst firing activity of thalamic neurons during various NREM sleep stages. 5,6 In parallel, studies mainly performed in primary sensory neurons [7][8][9][10] demonstrated that this low-threshold Ca 2C current, named T-type current, is activated around ¡60 mV and fully inactivated after a few tens of milliseconds. Since steady-state inactivation of these channels is nearly complete at membrane potentials more depolarized than ¡60 mV, a hyperpolarization that allows some channels to recover from inactivation is required before a substantial T-type current can be evoked.…”
mentioning
confidence: 99%